The Educational Context of Computer-Assisted Language Learning (CALL) - Jorge E. Benavides B. (Asociación Colombiana de Profesores de Ingles, 2016)
It is very common for many people to experience a great deal of excitement generated by rapid new technological developments and the ongoing need to think about how to fit this into existing systems. For the most part, this has resulted in a situation where almost all the energy is concentrated on the actual technology itself and not on the implications of its use. The resulting danger is that it is easy to be misled by the whole business and to become uncritically enthusiastic about future possibilities. It is important, then, to concentrate on the real purpose of using new technology so that quite a considerable investment of time, energy, enthusiasm and resources is worth the effort.